Revalidation and revision of the genus Magulla Simon 1892 (Araneae, Mygalomorphae, Theraphosidae) - Indicatti, Rafael P.; Lucas, Sylvia M.; Guadanucci, José P. L.; Yamamoto, Flávio U. (Zootaxa, 2008)
The genus Magulla Simon 1892 is revalidated and redescribed. The female of the type species M. obesa Simon 1892 is redescribed and the male is described for the first time. Magulla janeirus (Keyserling 1891) is considered a valid species. Magulla symmetrica Bücherl 1949 is transferred to Plesiopelma Pocock 1901, and considered a junior synonym of P. insulare (Mello-Leitão 1923). Additionally, two new species are described from Brazil: M. buecherli n. sp. from Ilhabela, São Paulo and M. brescoviti n. sp. from São Francisco de Paula, Rio Grande do Sul.